2017
DOI: 10.1111/pala.12335
|View full text |Cite
|
Sign up to set email alerts
|

Determining climate change impacts on ecosystems: the role of palaeontology

Abstract: Climate change is projected to change the ecosystems on land and in the sea at rates that are unprecedented for millions of years. The most commonly used approach to derive projections of how ecosystems will look in the future are experiments on living organisms. By their nature, experiments are unlike the real world and cannot capture the ability of organisms to migrate, select and evolve. They are often limited to a select few species and drivers of environmental change and hence cannot represent the complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 105 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…The time phase of remote sensing data does not reach a very high degree of closeness, and there is a certain error in the results of the analysis of RSEI. Moreover, climate change has an important impact on the quality of ecosystems and the ecological environment and should be considered in the future [ 69 , 70 ]. Limited by the number of data acquisitions, this study only studies the 2017 Qinling-Daba Mountains’ RSEI and its influencing factors and has not carried out multi-dimensional studies on multiple years to reveal its temporal and spatial distribution characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The time phase of remote sensing data does not reach a very high degree of closeness, and there is a certain error in the results of the analysis of RSEI. Moreover, climate change has an important impact on the quality of ecosystems and the ecological environment and should be considered in the future [ 69 , 70 ]. Limited by the number of data acquisitions, this study only studies the 2017 Qinling-Daba Mountains’ RSEI and its influencing factors and has not carried out multi-dimensional studies on multiple years to reveal its temporal and spatial distribution characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that change the ecological quality can be roughly divided into natural factors and human factors. Some studies have shown that climate has become a driving factor for changes in the ecological environment [23]. Compared with the SPEI-based drought characteristics reported by Yan et al [24] from 1958 to 2015, it has been found that the 2013 Mount Tai region was the worst drought in 13 years.…”
Section: Discussionmentioning
confidence: 85%
“…; Finnegan et al . ; Kidwell ; Schmidt ). With the looming threat of large‐scale disruption of global ecosystems, there is a need for palaeontologists to be bifocal: we need to zoom in to uncover the historical particulars of individual events, but also zoom out to search for underlying causal structures that may hold general lessons across multiple events.…”
Section: From Event‐based Reasoning To Dynamical Causalitymentioning
confidence: 99%